Pengaruh Penambahan Limbah Plastik Jenis Thermosetting Terhadap Parameter Marshall Laston AC-WC - Kusdiyono Kusdiyono; Supriyadi Supriyadi; Tedjo Mulyono; Sukoyo Sukoyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
At present, plastic is a material that is needed by the community at large, where the impact is also very extraordinary after the plastic is used in everyday life which can cause serious problems if the management is not done properly. The problem of plastic waste does not only occur in the city of Semarang, but also in other cities, so that the Ministry of Environment and Forestry has implemented a paid plastic bag program in the short term. But this is only to deal with problems in the short term. In the long run, it will not solve the problem of "plastic waste", because the policy actually encourages people to buy plastic which, of course, will add a new burden for the community to buy it. Based on the above problems, it is necessary to utilize this plastic waste to be made into road pavement materials such as in the manufacture of Asphal Concrette Wearing Course, by making 5 mixed variations ranging from (2 to 10)% of the weight of the aggregate . This research was initiated through a survey process, material procurement, testing of stacking materials, making test specimens, testing specimens. The results of the research can show that the type of Thermosetting plastic waste has a significant influence on the Asphalt Concrete mixture AC-WC heat mixture, including: Density, Marshall Stability, Flow, VIM, VMA, MQ and the remaining Marshall Stability tend to show an increase, moderate VFA and VIMrefusal Density values tend to show a decrease. Thus the plastic waste from the Thermosetting type can be used as a partial replacement of the aggregate for the Asphalt Concrete mixture AC-WC heat mixture with a plastic waste content is limited to a maximum of 10% and at an optimum asphalt content of 5.55%. Thus this research is expected to be of benefit to the industry and the people of Semarang in relation to the use of plastic waste for road pavement.